Stable Wide Input Delta-Sigma Analog To Digital Converters For Driving Single/Three Phase Switching Converters - K. , Diwakar (2010)
In this thesis, four Delta-Sigma Modulator (DSM) configurations, three multiplier configurations and a vector quantizer are proposed. These proposed modules are used to develop single phase/three phase switching converters (SCs) with single-input/multiple-inputs. The performance of SCs with proposed modules is better than the existing SCs.